The prevalence of burnout and its predictors among pharmacists working in government hospitals in Selangor - Subramaniam, Nivahsshinie; Mohd Sidik, Sherina; Chong, Seng Choi; Muthiah, Sri Ganesh (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: To determine the prevalence and predictors of burnout (personal, work-related and client-related) among pharmacists in government hospitals in Selangor. Methods: An analytical cross-sectional study was conducted among 376 pharmacists working in five government hospitals in Selangor. The data was collected via email using Google form containing self-administered questionnaires. Frequency and percentage of variables were obtained using descriptive statistics. Chi square was utilized to identify the relationship between factors. The significant predictors were determined using multiple logistic regression analysis. Results: Prevalence of burnout among pharmacist was reported as 52.9% (Personal), 66.0% (Work-related) and 47.1% (Client-related). The significant predictors of personal burnout were gender (AOR 2.24, 95% CI 1.29 to 3.89), working hours per week (AOR 2.92, 95% CI 1.60 to 5.32), job satisfaction (AOR 13.00, 95% CI 3.37 to 50.16) and depression (AOR 3.33, 95% CI 1.98 to 5.61). The significant predictors of work-related burnout for male was from work stress (AOR 9.10, 95% CI 3.12 to 26.60) and anxiety (AOR 5.91, 95% CI 2.03 to 17.25) while for female was from anxiety (AOR 5.91, 95% CI 2.86 to 12.23) and self-esteem (AOR 5.88, 95% CI 1.68 to 20.56). For client-related burnout, working hours per week (AOR 2.44, 95% CI 1.39 to 4.28), job satisfaction (AOR 3.91, 95 % CI 1.49 to 10.27) and anxiety (AOR 2.61, 95% CI 1.57 to 4.32) were the significant predictors. Conclusion: Burnout among pharmacists is crucial to be brought to highlight and it is necessary to perform appropriate interventions for managing the burnout.